2011
DOI: 10.1371/journal.pone.0026447
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Synchronisation of Anti-Predation Vigilance in Two Crane Species

Abstract: Much of the previous research on anti-predation vigilance in groups has assumed independent scanning for threats among group members. Alternative patterns that are based on monitoring the vigilance levels of companions can also be adaptive. Coordination of vigilance, in which foragers avoid scanning at the same time as others, should decrease the odds that no group member is alert. Synchronisation of vigilance implies that individuals are more likely to be vigilant when companions are already vigilant. While s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 43 publications
2
44
1
1
Order By: Relevance
“…Other studies have used snapshots of group behavior to determine whether individuals were exhibiting vigilant behavior at the same time more or less than would be predicted statistically. These studies provide evidence that animals do monitor their neighbors, and tend of synchronize, rather than asynchronize their vigilance (Beauchamp, 2009;Ge, Beauchamp, & Li, 2011;Pays, Renaud, et al 2007). We suggest that measuring gaze following could also provide a direct measure of visual monitoring.…”
Section: Visual Monitoring In Groupsmentioning
confidence: 84%
“…Other studies have used snapshots of group behavior to determine whether individuals were exhibiting vigilant behavior at the same time more or less than would be predicted statistically. These studies provide evidence that animals do monitor their neighbors, and tend of synchronize, rather than asynchronize their vigilance (Beauchamp, 2009;Ge, Beauchamp, & Li, 2011;Pays, Renaud, et al 2007). We suggest that measuring gaze following could also provide a direct measure of visual monitoring.…”
Section: Visual Monitoring In Groupsmentioning
confidence: 84%
“…It has also been suggested that by synchronizing their vigilance bouts, individuals could reduce the risk of being left behind during an attack, which could be dangerous if predators preferentially target laggards (Sirot and Touzalin, 2009). Vigilance synchronization has been documented in several species of birds and mammals, suggesting that monitoring neighbors is common in prey species (Fernández-Juricic et al, 2004;Pays et al, 2007aPays et al, ,b, 2009Pays et al, , 2012Beauchamp, 2009;Ge et al, 2011;Michelena and Deneubourg, 2011;Öst and Tierala, 2011;Butler et al, 2016;Podgórski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…; Ge et al. ; Brandl & Bellwood ). The rarity of cases for vigilance coordination could be explained by the cost of monitoring neighbors and organizing vigilance accordingly that may offset the associated benefits (Ward ).…”
Section: Introductionmentioning
confidence: 99%